IMPLEMENTATION OF INTERPRETATION IN IMPROVING UNDERSTANDING IN CONTEXTUAL-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE DIGITAL ERA - Nahuda, Nahuda (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This study explores the implementation of tafsir (Qur’anic interpretation) as a pedagogical strategy to enhance students’ understanding of Islamic Religious Education (PAI) through a contextual-based learning model in the digital era. The integration of thematic and contextual interpretation aims to bridge Qur’anic values with students’ real-life challenges, making religious learning more relevant and applicable. Employing a descriptive qualitative method, data were collected through observation, interviews, and documentation in a secondary Islamic school. The findings reveal that incorporating tafsir into PAI learning significantly improves students’ reasoning skills, contextual comprehension, and spiritual insight. Digital tools—such as interpretation apps, interactive videos, and online platforms—further enrich the learning experience. However, limitations persist, including low tafsir literacy among educators, insufficient contextual digital resources, and the need for professional development in integrating interpretation within the curriculum. This study concludes that the strategic application of contextual and technology-assisted tafsir holds considerable promise for enhancing the quality of Islamic education, provided it is supported by adequate resources and educator readiness.